1987
DOI: 10.1080/01431168708948611
|View full text |Cite
|
Sign up to set email alerts
|

Ground radiometry and airborne multispectral survey of bare soils

Abstract: Results are presented from studies of bare soils conducted during the NERC MSS-82, -83 and -84 campaigns. Test areas throughout southern and eastern England were selected to represent a wide range of British soils, and data from these sites are discussed in relation to the problems of intercalibrating ground and airborne data, as well as the effects of solar-sensor geometry on such intercalibration.Natural ground targets were used to intercalibrate the airborne data with ground radiometric measurements, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 7 publications
3
11
0
Order By: Relevance
“…The results have demonstrated that the approach provides useful data for describing soil surface structure. This result extends earlier multispectral MVA work with soils (Kimes et al 1980, Milton andWebb 1987) into an operational hyperspectral context. Three key points are important for end-users: first, the collimating lens should be used with Downloaded by [University of North Dakota] at 03:05 22 December 2014 the OO instrument, to ensure that data are collected from a well-defined small area on the target.…”
Section: Resultssupporting
confidence: 62%
“…The results have demonstrated that the approach provides useful data for describing soil surface structure. This result extends earlier multispectral MVA work with soils (Kimes et al 1980, Milton andWebb 1987) into an operational hyperspectral context. Three key points are important for end-users: first, the collimating lens should be used with Downloaded by [University of North Dakota] at 03:05 22 December 2014 the OO instrument, to ensure that data are collected from a well-defined small area on the target.…”
Section: Resultssupporting
confidence: 62%
“…The results of our experiment, as well as others carried out by Brennan and Bandeen (1970), Kriebel (1976), Kimes and Seller (1985), Walthall et al (1985 ), Milton and Webb (1987), and Irons and Smith (1990 ), show that the soil surface NR variation along the SPP in the view zenith angle h v function depends most strongly on the solar zenith angle h s , independent of its roughness state. To minimize the in uence of the h s on the variation of the NR curve shape, caused by the soil surfaces roughness, only the curves for which data were collected at similar solar zenith angles can be directly analysed together, as presented in gure 6.…”
Section: Evects Of Farming Work On the Soil Bidirectional Re Ectancementioning
confidence: 57%
“…The reflectance of bare soil in the visible and near-infrared range has mainly been discussed as a background for spectral response of vegetative surfaces (Brennan and Bandeen, 1970;Kriebel, 1976;Eaton and Dimhirn, 1979;Ott et al, 1984;Curran, 1985;Bartlett et al, 1986;Huete, 1987;Milton and Webb, 1987;Foody, 1988;Deering et al, 1990). Remotely sensed data on the soil surface, like vegetation canopies, demonstrate non-Lambertian reflectance properties.…”
Section: Results Of Soil Bidirectional Reflectance Measurementsmentioning
confidence: 98%
“…If position of irregularities of a rough surface makes it impossible to illuminate the whole surface directly, its shadowing becomes another important factor influencing the shape of the surface reradiation pattern (Graetz and Gentle, 1982;Cooper and Smith, 1985;Ranson et al, 1985;Huete, 1987;Milton and Webb, 1987;Cierniewski, 1987Cierniewski, , 1989Irons et al, 1992). The degree of surface shadowing depends on the density of those elements which cast the shadow, the microconfiguration of the surface, and its slope in relation to the incident rays.…”
Section: Reradiation Of Natural Surfacesmentioning
confidence: 98%